EFEKTIVITAS EKSTRAK BIJI PANGI (Pangium edule Reinw) TERHADAP MORTALITAS LARVA NYAMUK Anopheles - Viesta Sampe; Theopilus Watuguly (BIOPENDIX, 2016)
Background: Eradication of mosquito nests in Maluku is still done by fogging and with other chemicals. But on the other hand can cause disease in the respiratory tract and environmental damage. Pangi seeds contain alkaloids and potentially saponin compounds as larvacide to kill mosquito larvae. Method: The study design was using RAL (Completely Randomized Design) with 5 treatments ie K1 (control), K2 0,04%, K3 0,08%, K4 0,16% and K5 0,23% with each 25 larvae with 3 repetitions observed for 24 hours. One Way ANOVA Test Result and Probit LC50 Analysis were used to find out the extract of pangi seed which is effective in killing mosquitoes. Result: One Way ANOVA test result obtained Fcount value is 467.063 with Sig value. 0.000 and probit analysis obtained 24 hours LC50 value of 0.053% means that the extract of pangi seed (Pangium edule Reinw.) Is effective against mortality of Anopheles mosquito larvae. Conclusion: Seed extract (Pangium edule Reinw) effect on mortality of Anopheles mosquito larvae with LC50 extract value of Pangi (Pangium edule Reinw) in 24 hours was 0.053%. Each concentration of pangi seed extract (Pangium edule Reinw) had an effect on mortality of Anopheles mosquito larvae within 24 hours of observation time. There was a correlation between various concentrations of Pangi (Pangium edule Reinw) with the mortality of Anopheles mosquito larvae with value (p) = 0.000 and the relationship level was very strong with Pearson correlation value 0.891.